Furacão Katrina, as causas externas e as epidemias - Pinheiro Gawryszewski, Vilma; de Moraes, Flávia Aparecida; Suzuki, Eliana; Ciccone, Flávia Helena; Vilaça, Pedro José (BEPA. Boletim Epidemiológico Paulista, 2005)